GORLIVKA CHEMICAL FACTORY AS A SEAT OF THE MAN-CAUSED LOADING ON ENVIRONMENT - KURAIEVA, I.; SAMCHUK, A.; YAKOVENKO, O.; KYSELOV, M.; FILATOV, V.; DUBROVA, N.; VOITIUK, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Regularity of distribution of heavy metals in soils and wastes of Gorlivka Chemical Factory has been investigated.